A1.17 Podoplanin and its ligand CLEC-2 restrain synovial inflammation. (24th February 2016) - Desanti, GE; Naylor, AJ; Núñez, L Navarro; Saghir, AN; Hardie, DL; Watson, SP; Buckley, CD
Abstract : Background and objectives: During synovial inflammation, platelets and their microparticles escape from the vasculature to fuel the synovial membrane with pro-inflammatory factors leading to the activation of synovial fibroblasts (SF) that actively contribute to joint damage. 1 Patients with rheumatoid arthritis (RA) show an up-regulation of surface protein Podoplanin (PDPN) on SF. 2, 3 Although the function of PDPN is still poorly understood, recent data suggest that PDPN ligation to its ligand CLEC-2 can modulate cellular responses. Within the RA synovium, platelets are considered the sole source of CLEC-2. 3 Despite these observations, clear experimental approaches that explore the role of PDPN/CLEC-2 interactions in RA are lacking. Materials and methods: PDPN expression by freshly isolated mouse synoviocytes was measured by flow cytometry during joint inflammation and after resolution. Tamoxifen-inducible Clec1b deletion mice (TIC mice) were used to assess the disease severity in absence of CLEC-2. CLEC-2 deletion was confirmed on circulating platelets by flow cytometry. Arthritis was induced by anti-collagen antibodies and LPS injections. The disease severity was monitored by body weight, clinical scores, ankle and paw thicknesses. Bone erosion and bone remodelling were studied by MicroCT scans and 3D reconstructions. Results: Joint inflammation triggers PDPN up-regulation on SF and an accumulation of PDPN+ leucocytes in the synovium. These high levels of PDPN expression disappear when inflammation resolved. In absence of CLEC-2, arthritis is more severe, bone erosion and bone remodelling are more pronounced. Conclusions: In this work, we provide the first in vivo evidence that PDPN/CLEC-2 interactions act to restrain arthritis by showing that ablation of CLEC-2 expression leads to worse arthritis, bone erosion and bone remodelling. These observations suggest that platelets, known for promoting joint inflammation, also contribute to the suppression of arthritis in a CLEC-2 dependent manner. The mechanisms underlying this anti-inflammatory process are currently under investigation. References: Boilard E, et al . Nat Rev Rheumatol. 2012;8:534–542 Ekwall AK, et al . Arthritis Res Ther . 2011;13 :R40 Del Rey MJ, et al . PLoS One. 2014;9 :e0099607